(untitled) (Research, Society and Development, 2021)
Despite the difficulty of conceptualizing the Solidarity Economy (SE) due to interconnected themes and used interchangeably, it is mistaken in isolation from the context of economic development as an alternative for generating family income. With the social and economic reality of the regions of the extensive Brazilian territory, there is a blurring of the social function that HE plays in the field of Public Policies that make up family farming, which, among other developments in terms of government policies, is foreseen as one of the goals of the 17 Sustainable Development Goals for 2030, of the United Nations, characterized as a national and international development instrument. The method consists of descriptive and documental analysis, using a quantitative and bibliographic approach regarding the representation of data. A misalignment of the axes that foster public policies with sustainable development was found, and higher education was forgotten and to a certain extent suffocated by the capitalist system in which inclusive public policies are unable to absorb this phenomenon. There are limited feasible strategic policies to rescue simple forms of work and income such as Solidarity Economic Enterprises (SEE). This discussion has been going on for at least a century, and until the first decade of the 21st century, strategic lessons were not learned for the inclusion of family farming as an alternative for rural families who live on subsistence. The importance of the theme is highlighted due to the social inequality that Brazil faces as a chronic problem, as thousands of families live off initiatives such as higher education for subsistence.